PERFORMANCE OF INSTITUTIONAL EFFORTS IN PREVENTING MARRIAGE UNDER THE AGE OF 19 - Yola Shofia Putri Hasibuan; Asima Yanty Sylvania Siahaan (Jurnal Kebijakan Publik, 2025)
This research focuses on analyzing the performance of the Office of Population Control, Family Planning, Women’s Empowerment, and Child Protection (DP2KBP3A) in Asahan Regency in its efforts to prevent marriages under the age of 19. Child marriage is a complex social issue in Indonesia and various other developing countries, with significant impacts on multiple aspects of life, including reproductive health, education, economics, and social welfare. In Asahan Regency, although there has been a decline in the number of marriages under the age of 19 in recent years, this issue remains prevalent. This study uses a descriptive qualitative approach with data collection techniques through in-depth interviews with key informants, including DP2KBP3A staff, the community, and program participants, as well as document analysis and direct observation. The data sources include primary and secondary data, collected through observation, documentation, and interviews. The data analysis technique includes data reduction, data presentation, and data verification. The results show that DP2KBP3A has implemented various preventive efforts through the Generation Planning (GenRe) program, focusing on raising awareness about the dangers of early marriage among adolescents and families, increasing access to education, and providing reproductive health counseling. However, field implementation faces several challenges, such as low public awareness of the importance of preventing early marriage, minimal economic support for at-risk families, and the strong influence of cultural norms that still support underage marriage. From this analysis, the main recommendations proposed include enhancing coordination between government agencies, increasing reproductive health education programs for adolescents, empowering economically vulnerable families, and using community-based approaches to address cultural norms that support child marriage.